Natural course of patients diagnosed with nodular fasciitis - Hiroshi Urakawa; Kunihiro Ikuta; Tomohisa Sakai; Hiroshi Koike; Takeo Fujito; Yoshihiro Nishida; Shiro Imagama (BMC Musculoskeletal Disorders, 2025)
Abstract Background Nodular fasciitis (NF) shrinks spontaneously; however, few reports have focused on its self-regression. This study investigated NF shrinkage. Methods We retrospectively reviewed 55 patients with NF who visited Nagoya University Hospital. Twenty-three patients were followed-up and evaluated for shrinkage. Factors affecting the occurrence of deep layers and ≥ 50% tumor volume shrinkage were investigated. The proportion of patients who achieved ≥ 50% tumor volume shrinkage, time to ≥ 50% tumor volume shrinkage, and tumor volume compared with baseline at the last follow-up were assessed. Results The presence of deep layers was significantly associated with longer symptom duration and more frequent biopsies. The proportion of patients who achieved ≥ 50% tumor volume shrinkage, time to ≥ 50% tumor volume shrinkage, and tumor volume compared to baseline at the last follow-up were 17 of 23 patients (74%), median 104 days (19–973)days, and median 24% (7–99%), respectively. Shorter duration of symptoms was significantly associated with ≥ 50% tumor volume shrinkage. Conclusion Approximately three-quarters of the patients demonstrated ≥ 50% tumor volume shrinkage, suggesting that wait-and-see concept was acceptable for NF. The better understanding of NF shrinkage showed that proper follow-up is necessary for patients with NF.